2014
DOI: 10.1177/2158244014525415
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Students’ Perceptions of Online Teamwork

Abstract: The evolution of online teaching in higher education demands a change in the types of pedagogies used in those courses. An example of one of these important pedagogies includes online teamwork. Teamwork in this context is one in which the majority of the individual’s grade is dependent on the positive or negative group experiences. This study utilized the theoretical framework of social motivation and cohesion to identify the factors shaping students’ perceptions of teamwork in online college courses. In these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Students' previous engagement in learning teamwork KSAs can certainly have an effect on teamwork attitudes, teamwork self-efficacy and online teamwork self-efficacy. Learning teamwork KSAs can make a positive impact on students' perceptions of teamwork (Falls et al, 2014). Compared to face-to-face students, online students may not have the same opportunities to learn teamwork KSAs.…”
Section: Research Model and Backgroundmentioning
confidence: 99%
“…Students' previous engagement in learning teamwork KSAs can certainly have an effect on teamwork attitudes, teamwork self-efficacy and online teamwork self-efficacy. Learning teamwork KSAs can make a positive impact on students' perceptions of teamwork (Falls et al, 2014). Compared to face-to-face students, online students may not have the same opportunities to learn teamwork KSAs.…”
Section: Research Model and Backgroundmentioning
confidence: 99%
“…Students' perceptions towards teamwork may be influenced not only by their personality (Myers et al 2009) or communication skills (De Rosa andLepsinger, 2010) but also by their experience on team-working (Falls et al 2014); a skill that it is not lectured but learned by doing.…”
Section: A Drawback For Most Of Them Was the Methodological Strategy mentioning
confidence: 99%
“…Falls et al (2014) concluded that students' perception of group work is influenced by personal factors and that this perception affects student performance as group members.…”
Section: Perceived Benefits and Risks Of Group Workmentioning
confidence: 99%